2009
DOI: 10.1007/s00384-009-0658-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgeons lack predictive accuracy for anastomotic leakage in gastrointestinal surgery

Abstract: Background The dramatic clinical consequences of anastomotic leakage in gastrointestinal surgery can be reduced by a diverting stoma or drainage of the peri-anastomotic area. Currently, the surgeons' clinical judgement is of major importance in decision making, but reliable data of the diagnostic accuracy are lacking. In this prospective clinical study, the surgeons' predictive accuracy for anastomotic leakage was evaluated. Materials and methods In 191 patients undergoing colorectal resection with anastomosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
263
0
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 387 publications
(278 citation statements)
references
References 23 publications
3
263
0
12
Order By: Relevance
“…The imaging systems are typically sufficiently compact and portable to be brought into the operating room and can provide images rapidly and conveniently, in a manner similar to intraoperative ultrasound (24). Optoacoustic imaging could assess the perfusion status of tissue by detecting hemoglobin dynamics and oxygenation, potentially providing better prediction of anastomotic leakage resulting from ischemic conditions in the colon or esophagus while it can still be prevented (83).…”
Section: Intraoperative Imagingmentioning
confidence: 99%
“…The imaging systems are typically sufficiently compact and portable to be brought into the operating room and can provide images rapidly and conveniently, in a manner similar to intraoperative ultrasound (24). Optoacoustic imaging could assess the perfusion status of tissue by detecting hemoglobin dynamics and oxygenation, potentially providing better prediction of anastomotic leakage resulting from ischemic conditions in the colon or esophagus while it can still be prevented (83).…”
Section: Intraoperative Imagingmentioning
confidence: 99%
“…Assessment of the perfusion of an organ post-transplant, for example, provides an indicator of the efficacy of the vascular anastomoses 1 . Similarly, imaging of the microperfusion in the perianastomotic region following bowel resection and reattachment surgery may also allow prediction of areas at risk of leakage 2 , thus preventing subsequent complications 3 .…”
Section: Introductionmentioning
confidence: 99%
“…He then reviewed the known and controversial risk factors for anastomotic leak. He presented data from a prospective study assessing whether surgeons, at the time of anastomotic construction, can predict which patients will leak [10]. Results demonstrated that surgeons cannot predict which patients will leak.…”
Section: Doctor Hans Schardey and Doctor James Fleshman Presentationmentioning
confidence: 99%